Effectiveness of lotus and duckweed in ferum removal to improve greywater quality - Hamidon, Nuramidah; Embline, Tan Sze Yee; Mohamed Sunar, Norshuhaila; A. Hamid, Nor Hazren; Muhamad, Mimi Suliza; Harun, Hasnida; Ali, Roslinda; Awang, Mariah (WARSE, 2020)
The broad environmental issue for surface water is the water pollution and always due to various industrial and domestic activities that produce liquid waste. The untreated wastewater that contain high concentration of ferum can lead to the damage healthy skin cells, causes of residue inside the pipes. Besides that, the The untreated greywater that contain high concentration of ferum can cause the growth rate of the plants reduced and affect the growth of aquatic organisms. The goal of this study is to test the greywater quality after planting lotus in the sample greywater. The parameters tests include the pH, biological oxygen demand (BOD) and chemical oxygen demand (COD), turbidity, concentration of ferum, dissolve oxygen (DO), ammoniacal nitrogen (AN) and total suspended solids (TSS) of the sample greywater, before and after planted with lotus. The sample greywater tested for 3 days and 7 days after planted with the lotus to identify whether the duration of treatment can improve the water quality. This study also includes compare the effectiveness of lotus and duckweed in improving the quality of sample greywater. Results from the experiment showed that the lotus had the ability to reduce ferum and improve quality in the greywater to standard A. Besides that, the quality of sample greywater keeps on improving with the longer time planted with lotus. The sample greywater had the better quality after 7 days planted with lotus compare to the greywater that had planted by lotus for 3 days. For example, the concentration of ferum in greywater sample recorded as 0.28mg/L and reduced to 0.80mg/L after 7 days planted with lotus. The duckweed had the better ability to remove ferum and turbidity in the greywater whereas lotus had the better ability in increasing the DO and reducing the BOD and COD of the sample greywater. The percentage of duckweed in ferum removal recorded as 77.06% which is 50.45% higher than lotus.